1996
DOI: 10.1007/bf00266818
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic extradural hematomas of the posterior fossa in children

Abstract: The most favorable type of traumatic intracranial bleeding in childhood is the extradural hemorrage (EDH). The posterior fossa location is less frequent than the supratentorial site. In the period from January 1989 to January 1994 we treated 2,372 patients with craniocerebral trauma; 31 had extradural hematomas (1.3%); 3 of them were located in the posterior fossa (9.7%): 1 boy and 2 girls aged from 6 to 16 years. The traumatic mechanism was an occipital fall in all cases. Diagnosis was made by computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…A number of studies on PFEDH can be found in the literature; however, exclusively pediatric case series are fewer in number [1,2,3,6,7,8,9,10]. To date, reports of around 140 pediatric cases have been published in English [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies on PFEDH can be found in the literature; however, exclusively pediatric case series are fewer in number [1,2,3,6,7,8,9,10]. To date, reports of around 140 pediatric cases have been published in English [2].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is urgent surgical evacuation, except occasionally, when it consists of management along conservative lines [1,2]. A few series have reported the outcomes of such traumatic lesions in children [1,2,3,6,7,8,9,10]. The aim of this study was to analyze the outcomes for children with PFEDH who were managed at our apex trauma center and to compare our results with published reports.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[37] In about 80% of cases, there is an occipital fracture. [38] Because of the risk of rapid clinical deterioration due to brainstem compression, timely surgery can be life-saving.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Although some patients have been successfully treated with conservative approach, 5 , 13 most studies support timely management of PFEDH by surgical intervention in children. 5 , 7 , 14 , 15 , 16 , 17 For EDH, standard craniotomy is routinely used to remove the hematomas. 18 There are also several reports on the successful applications of trephination mini-craniectomy for evacuation/drainage of the hematomas in adult patients under emergency setting.…”
Section: Introductionmentioning
confidence: 99%